2020
DOI: 10.5513/jcea01/21.1.2777
|View full text |Cite
|
Sign up to set email alerts
|

Postharvest quality of 'Granny Smith' apple grown under photo-selective red net

Abstract: The present study was conducted with aim to test the effect of red photo-selective nets (Agritech S.r.l., Eboly, Italy) on 'Granny Smith' apple postharvest quality. The fruits have been harvested on optimal harvest date from orchard near city of Zadar where red photo-selective nets were used. Afterwards fruits were stored in regular air storage at 0°C for 4 months and then kept for 7 days at room temperature (shelf life). After harvest, cold storage and shelf life fruits grown under red net had significantly l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…The effect of net application on the fruit size of different fruit species has been extensively studied; however, results are diverse, probably due to the variability of agroecological conditions, net properties, fruit species, varieties, etc. Generally, in most cases, the application of nets caused, fully or partly (depending on fruit variety and net type), an increase in fruit size or mass [5,16,22,25,32,39,[58][59][60][61]116]. Only Bosco et al [4] reported a fully negative impact, while, in other studies, this impact was not recorded [26,43,117], was mixed (positive and negative), or could not be assessed due to lack of a control group (open-field conditions) [19,21,54,57,118].…”
Section: Fruit Sizementioning
confidence: 99%
See 3 more Smart Citations
“…The effect of net application on the fruit size of different fruit species has been extensively studied; however, results are diverse, probably due to the variability of agroecological conditions, net properties, fruit species, varieties, etc. Generally, in most cases, the application of nets caused, fully or partly (depending on fruit variety and net type), an increase in fruit size or mass [5,16,22,25,32,39,[58][59][60][61]116]. Only Bosco et al [4] reported a fully negative impact, while, in other studies, this impact was not recorded [26,43,117], was mixed (positive and negative), or could not be assessed due to lack of a control group (open-field conditions) [19,21,54,57,118].…”
Section: Fruit Sizementioning
confidence: 99%
“…Accordingly, there are conflicting reports regarding shading's influence on fruit firmness. Similarly, there is no general consistency between studies regarding net influence on fruit firmness of apples [4,19,26,32,42,57,59,109,116,124,154], peaches [8,16,61,125], or other fruit species [5,21]. Therefore, other possible mechanisms should also be taken into account.…”
Section: Fruit Firmnessmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, it should be further noted that there is a lack of studies that deal with an effect of photoselective nets on the apples' bioactive compounds. In our previous studies, the red photoselective anti-insect net exerted a satisfactory pre-harvest effect on the ´Cripps Pink´ apple, ´Sugar Time´ peach, and the ´Big Bang´ nectarine (Brkljača et al, 2016;Vuković et al, 2016), an optimum effect on post-harvest performance of the ´Granny Smith´ apple (Vuković et al, 2020), and the satisfactory pest control properties (Pajač Živković et al, 2016(Pajač Živković et al, , 2018. Consequently, the present work is an extension to our previous studies.…”
Section: Introductionmentioning
confidence: 98%